Οι απόψεις της κύπριας γυναίκας σε σχέση με τη διασφάλιση του δικαιώματος επιλογής τόπου τοκετού - Χατζηγεωργίου, Ελένη (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
Childbirth is one of the most important events in women's life and its experience has direct impact on women's and newborns' health. Β1rthplace is considered a determining factor for women's positive experience of birth. Positive childbirth experience empowers women and strengthens the bond between her, her newborn and her family. The World Health Organization, in recognition of the important benefits of strengthening this bond and aiming at improving maternity care, recommended creating mechanisms for ensuring the childbirth rights, particularly the right to choose place of birth. In Cyprus, no research has been found for maternity care provision, in general and choice of birth place, in particular. Exploring Cypriot women's experiences towards their right for birth place choices is essential, both socially and politically. The implementation of further research will strengthen more the national health care policy in the reformation of maternity care.Purpose: The purpose of this study was to investigate Greekcypriot's women perceptions towards their right for birth place choices. Material and Methods: This study is qualitative and is based on Husserl's phenomenological approach. The sampling was purposive and consisted of 55 women who had delivered a full term neonate, without pathological or surgical problems in the past 12 months in Cyprus. 48 women took place with semi-structured interviews and 6 of them took place in first focus groups. The second group consisted of 7 women. The data analysis for the interviews was conducted according to Collaizi's method and for the focus group with content analysis. Results: Women's perceptions were categorized into five themes: 1. Informed choice for birth place 2. Birth culture, 3. Women's relationship with health professionals, 4. Safety of mother and newborn, 5. Maternity care policy. The most important factors influencing women's choice of birth place were: a) information, b) relationship of women with health professionals, c) maternity care policy in Cyprus. Although, the information has been documented as a key factor in choosing birth place, Cypriot women do not have access to objective and accurate information. The relationship of women with health professionals has been identified as a key factor choosing birth place. Most women have reported the role of obstetricians and very few knew about midwives. Midwives in Cyprus can not offer birth place choices and this is related with the maternity care policy. Conclusions: The maternity care provided in Cyprus is not fair and streamlined, as it does not provide correct information and accessibility to all birth place choices. The study demonstrated the need to explore women's views before formulating policy for maternity care. This study may be considered innovative for Cyprus, because for the first time Greekcypriot women had the opportunity to express their views in relation to maternity care. These views will be helpful for the creation of an innovative evidenced based maternity care policy, taking in account women's needs and will be helpful to raise awareness among health professionals for maternity care improvement. Conclusively, ensuring the right for birth place choices is a social and political necessity which enhances the existing health systems and health professionals to provide quality and holistic maternity care. Conducting more studies οn maternity care in Cyprus will reinforce the aim for improving the health of the women, neonates and society.
Keywords: Childbirth; Cypriot women; Birth place; Τοκετός; Κύπριες γυναίκες; Τόπος τοκετού